Systemic juvenile rheumatoid arthritis in an 11 year old boy: a case report - I Wayan Gustawan; Ketut Dewi Kumara Wati; Hendra Santosa (Indonesian Pediatric Society, 2009)
Juvenile rheumatoid arthritis (JRA) is the mostcommon rheumatic condition in childrenand a major cause of chronic disability. 1 JRAis defined as persistent arthritis in one oro e joints for at least six weeks, when certainexclusionary conditions have been eliminated.2Â·3The three major subtypes of JRA are based onthe symptoms at disease onset and are designatedas systemic onset, pauciarticular onset, andpolyarticular onset.2 Systemic onset juvenilerheumatoid arthritis (SoJRA) represents about10-20% of all forms of JRA.4The incidence of ]RA is approximately 13.9/100,000 per year among children 15 years old oryounger.1 In Finland, the incidence was 19.5/100,000of the population under 16 years of age. The incidencewas significantly higher than in earlier years (1980,1985, and 1990) in the same district.5 Different racialand ethnic groups appear to have varying frequenciesof the subtype of JRA.1The treatment of JRA is achieved usingcombinations of anti-inflammatory and immunomodulatorymedications in combination withphysical and occupational therapy, occasionalsurgery, nutritional support, and psychosocial andeducational partnerships with patients and parents.3,6It is widely thought that a comprehensive teamapproach is associated with a superior outcome. 7This paper reports a case of systemic JRA in an 11-year old boy.